Developing Tourist Village as an Alternative Tourist Destination - Saragi, Herbin (Interdisciplinary Social Studies, 2022)
Background: The increasing volume of tourists coming to Indonesia raises rural motivation to make economic improvements through the tourism village program. All villages can develop this tourist village to create alternative tourist destinations. However, the development of alternative tourist destinations is not an easy thing. Therefore, researchers want to find out more about the development of tourist villages as alternative tourist destinations. Aim: This study aims to find out how to open alternative tourist destinations by conducting an in-depth analysis to minimize the failure of developing alternative tourist destinations. Method: The method used in the research is descriptive qualitative and literature study. Data collection techniques using interviews, observation, and documentation then the data obtained will be analyzed in depth and delivered in easy-to-understand sentences. Findings: The results show that the development of tourist villages to create alternative tourist destinations cannot be separated from 3 principles: open and voluntary membership, democratic organizational management, and village independence. In addition, it must also refer to several things, namely: the attractiveness of a tourist attraction or its uniqueness, accessibility for visitors, the availability of various facilities that support tourists, community empowerment that is carried out on an ongoing basis, as well as marketing and promotion on an ongoing basis.